The pattern of Ki-67 and bcl-2 expression in Lymphoid Malignancies - Wang, P.L.; Peh, S.C. (1997)
The International Working Formulation divides non-Hodgkin's lymphoma (NHL) into three grades: low, intermediate and high. This grading system implies rate of tumour growth and hence prognosis. Ki-67 antigen is a proliferation-related nuclear antigen and bcl-2 oncogene product is known to inhibit apoptosis. This study aimed to detennine the pattern of expression of Ki-67 antigen and bcl-2 oncoprotein in various grades of NHL. Paraffin-embedded tissues from 42 cases of NHL (7 low, 15 intermediate, 20 high grade) were retrieved from the files of the Department of Pathology, University of Malaya. Ki-67 antigen and bcl-2 oncoprotein were detected using immunohistochemistry. The percentage of positively stained neoplastic cells was determined by semi-quantitative estimation and given scores ranging from 0 to 6. Partition chi square test demonstrated the association of Ki- 67 antigen expression and histological grade (p=0.007). There was no significant difference in Ki-67 antigen expression between intermediate and high grade malignant lymphomas (p=0.28), whereas significant difference was demonstrated between low and intermediatethigh grade tumours@=0.003).Bcl-2 oncoprotein expression in the neoplastic cells varied widely within the three histological grades. Statistical analysis showed no association between the expression of bcl-2 oncoprotein and histological grade (p=0.25). Ki-67 immunostaining is therefore a useful adjunct to histological grading of NHL.